Murabahah Sebagai Solusi Pembiayaan Syariah: Alternatif Jual Beli Bebas Riba Untuk Kebutuhan Konsumtif Dan Produktif - Irmawanti, Irmawanti; Winario, Mohd (Journal of Economic, Management, Business, Accounting Sustainability, 2025)
This study aims to analyze the role of the murabahah contract as a Sharia-compliant financing solution free from riba (usury) in meeting both consumptive and productive needs of the community. Murabahah, a sale contract with an agreed profit margin between Islamic banks and customers, has become one of the dominant instruments in the Islamic finance industry. This research adopts a qualitative descriptive approach through literature study. Data sources include books, scholarly journals, fatwas from the National Sharia Council of Indonesia (DSN-MUI), and reports from Islamic finance practitioners. The findings indicate that the murabahah contract is highly flexible in financing various needs, ranging from household consumer goods purchases to working capital financing for MSMEs. Furthermore, murabahah offers profit margin certainty and is free from riba, aligning with Sharia principles. Nevertheless, challenges remain in its implementation, such as the potential for practical deviations and the low public literacy regarding Sharia contracts. Therefore, strict supervision and continuous education are needed to ensure that murabahah truly serves as a fair and sustainable solution within the Islamic financial system.